2011
DOI: 10.1007/s00202-011-0208-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two methods for magnetic field synthesis on a solenoid’s axis

Abstract: Magnetic field synthesis problems have been discussed at length in scientific literature but they still remain as a topic of research in electrical engineering, physics and medical applications. In these disciplines, there is often a need to design an electromagnetic arrangement which can generate a magnetic field of required distribution. Such an arrangement can also work as an active shield. The aim of an active shield is to generate a specified magnetic field which counteracts the external magnetic fields i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…1. A definition sketch for a solenoid of unknown shape r = f (z') and solenoid's thickness t By using the formula for the magnetic field intensity on the circular loop axis, it can be shown that the magnetic field intensity vector on the solenoid axis has a simple form (only z-component exists) [1]:…”
Section: Problem Descriptionmentioning
confidence: 99%
See 4 more Smart Citations
“…1. A definition sketch for a solenoid of unknown shape r = f (z') and solenoid's thickness t By using the formula for the magnetic field intensity on the circular loop axis, it can be shown that the magnetic field intensity vector on the solenoid axis has a simple form (only z-component exists) [1]:…”
Section: Problem Descriptionmentioning
confidence: 99%
“…The Fredholm equation of the first kind belongs to the class of ill-posed inverse problems as defined by Hadamard. In order to solve (3) well known iteratively regularized Gauss-Newton can be applied [1]. However, such a deterministic approach is possible, when during optimization process t parameter has an assumed constant value.…”
Section: Problem Descriptionmentioning
confidence: 99%
See 3 more Smart Citations